Perfil clínico, epidemiológico e terapêutico da lacaziose no Serviço de Dermatologia da Universidade Federal do Pará no período de 1997 a 2011. - MENDES, Laís Ferreira (2023)
Introduction: Lacaziose is a chronic disease, localized or disseminated, characterized by lesions similar to a keloid, nodular or verrucous. It is a disease caused by infection Lacazia loboi (L. loboi) that affects mainly rural workers who live in contact with vegetation and soil, such as rubber tappers in the Amazon. Maybe that’s why it is more frequent in males. By October 1995 there were 418 reported cases, with 255 of them in Brazil. General Objetive: To describe the clinical, epidemiological and therapeutic in patients diagnosed with lacaziose Department of Dermatology Federal University of Pará (SDUFPA). Specific Objectives: To describe the sociodemographic profile of carriers of lacaziose; identify possible ways of transmission of the disease; to observe the dermatological characteristics of the presented cases; knowing the therapeutic response of patients; assess treatment compliance. Methodology: This is a clinical, epidemiological, cross-sectional, retrospective, descriptive and observational study using medical records of patients in lacaziose SDUFPA from January 1997 to july 2011. Results: We analyzed 16 patients in lacaziose SDUFPA. There was a predominance of males (81.25%), age of more than 60 years (56.25%) and from the interior of Pará (87.5%), the annual distribution of cases showed homogenous over the 14 years, most of the visits occurred in 2008 (18.75%). The highest prevalence of cases was observed in rural workers (62.5%), mostly married (56.25%). The lower limb injuries were most common (47%), with predominance of localized lesions (61.9%), followed by disseminated (24%) and more was found to keloid (61.1%). Pruritus was the most frequent symptom (62.5%) and ulceration was the main complication (55.5%). The combination of medical and surgical treatment predominated (43.7%). Clofazimine was the most used drug (31.2%) and the procedure most widely adopted surgical excision (76.9%). Recurrence after surgical treatment occurred in most patients (80%). Conclusion: Lacaziose is a little known disease in relation to transmission, pathophysiology and treatment. It is necessary that more studies be conducted in orde to discover the source of infection and interrupt the chain of transmission, and allow the emergence of more effective therapeutic measures.